GROUNDS AND CONDITIONS OF PLACING A PERSON IN A MEDICAL INSTITUTION FOR IMPLEMENTATION OF EXAMINATION - Vardanyan, Arnold (State and Law, 2020)
In the submitted article, the author discusses the conceptual peculiarities of placing a person in a medical institution for implementation of examination and presents a framework of relevant grounds and conditions. The author analyzes a number of problematic issues related with the procedure of placement of a person in a medical institution for implementation of examination. The author provided justifications for the necessity to reform the legal regulations concerning the procedure of placing a person in a medical institution for implementation of examination.